Major cereal crops benefit from biological nitrogen fixation when inoculated with the nitrogen-fixing bacterium Pseudomonas protegens Pf-5 X940 - Fox, Ana Romina; Soto, Gabriela Cinthia; Valverde, Claudio Fabián; Russo, Daniela Marta; Lagares, Antonio; Zorreguieta, Ángeles; Pascuan, Cecilia Gabriela; Frare, Romina Alejandra; Mercado Blanco, Jesús; Dixon, Ray; Ayub, Nicolás Daniel; Alleva, Karina Edith (2017)
A main goal of biological nitrogen fixation research has been to expand the nitrogen-fixing ability to major cereal crops. In this work, we demonstrate the use of the efficient nitrogen-fixing rhizobacterium Pseudomonas protegens Pf-5 X940 as a chassis to engineer the transfer of nitrogen fixed by BNF to maize and wheat under non-gnotobiotic conditions. Inoculation of maize and wheat with Pf-5 X940 largely improved nitrogen content and biomass accumulation in both vegetative and reproductive tissues, and this beneficial effect was positively associated with high nitrogen fixation rates in roots. 15N isotope dilution analysis showed that maize and wheat plants obtained substantial amounts of fixed nitrogen from the atmosphere. Pf-5 X940-GFP-tagged cells were always reisolated from the maize and wheat root surface but never from the inner root tissues. Confocal laser scanning microscopy confirmed root surface colonization of Pf-5 X940-GFP in wheat plants, and microcolonies were mostly visualized at the junctions between epidermal root cells. Genetic analysis using biofilm formation-related Pseudomonas mutants confirmed the relevance of bacterial root adhesion in the increase in nitrogen content, biomass accumulation and nitrogen fixation rates in wheat roots. To our knowledge, this is the first report of robust BNF in major cereal crops.